2007
DOI: 10.1063/1.2425004
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent electrical characteristics of bulk GaN Schottky rectifier

Abstract: The temperature-dependent electrical characteristics of Schottky rectifiers fabricated with a SiO2 field plate on a freestanding n− gallium nitride (GaN) substrate were reported in the temperature range of 298–473K. The Schottky barrier heights evaluated from forward current-voltage measurement revealed an increase of Schottky barrier height and series resistance but a decrease of ideality factor (n) with increasing temperature. However, the Schottky barrier heights evaluated from capacitance-voltage measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(39 citation statements)
references
References 28 publications
3
35
0
1
Order By: Relevance
“…The bowing of the experimental ln(I 0 /T 2 ) vs. 1/T plot can be associated with the temperature dependence of the effective SBH and ideality factor. As will be discussed later, deviation in the Richardson plots may be due to the laterally inhomogeneous barrier heights and potential fluctuations at the interface that consist of low and high barrier areas, that is, the current through the diode will flow preferentially through the lower barrier in the potential distribution [23,[26][27][28][29][30][31]. Zhou et al [30] reported that the value of A n determined by a modified Richardson plot in freestanding GaN material is close to the theoretical value.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…The bowing of the experimental ln(I 0 /T 2 ) vs. 1/T plot can be associated with the temperature dependence of the effective SBH and ideality factor. As will be discussed later, deviation in the Richardson plots may be due to the laterally inhomogeneous barrier heights and potential fluctuations at the interface that consist of low and high barrier areas, that is, the current through the diode will flow preferentially through the lower barrier in the potential distribution [23,[26][27][28][29][30][31]. Zhou et al [30] reported that the value of A n determined by a modified Richardson plot in freestanding GaN material is close to the theoretical value.…”
Section: Resultsmentioning
confidence: 55%
“…As will be discussed later, deviation in the Richardson plots may be due to the laterally inhomogeneous barrier heights and potential fluctuations at the interface that consist of low and high barrier areas, that is, the current through the diode will flow preferentially through the lower barrier in the potential distribution [23,[26][27][28][29][30][31]. Zhou et al [30] reported that the value of A n determined by a modified Richardson plot in freestanding GaN material is close to the theoretical value. On the other hand, Demirezen and Altındal [31] stated that the values of Richardson constant obtained from two linear regions for (Ni/Au)/Al 0.22 Ga 0.78 -N/AlN/GaN SBDs were found to be 3.25 Â 10 À 12 and 1.28 Â 10 À 9 A cm À 2 K À 2 , respectively, which are much lower than the theoretical value of 27.64 A cm À 2 K À 2 .…”
Section: Resultsmentioning
confidence: 55%
“…Arehart et al 19 studied the impact of threading dislocation density on the Ni/n-type GaN Schottky diode using forward currentvoltage-temperature measurements. Zhou et al 20 investigated the electrical characteristics of Schottky rectifier with a SiO 2 field plate on a freestanding n-type GaN in the temperature range of 298-473 K and reported that the barrier height increases and ideality factor decreases with temperature. The temperature dependence of the I-V characteristics allows us to understand different aspects of conduction mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Freestanding GaN substrates allow for vertical geometry devices and due to decreased dislocation density, the possibility of better performance. Recently such diodes have been investigated, [10][11][12][13] with high breakdown voltages being measured. These devices have relatively large on-state resistance due to the low doping level in the substrate.…”
mentioning
confidence: 99%